(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to model the lactation curves of Friesian-Holstein cows to estimate key curve characteristics and to quantify the effects of sire, dam, parity, and year of calving on these parameters.A total of 290 lactation records from 85 cows (progeny of 34 sires) were collected from the Alexandria University herd between 2003 and 2013. The incomplete Gamma function (Wood’s model) was fitted to individual lactation data to derive parameters: initial yield (a), ascending rate to peak (b), and post-peak decline rate (c). These were used to calculate total milk yield (TMY), peak yield (PMY), time to peak (PW), lactation length (LL), and persistency measures (LnS, PER). Data were analyzed using an ANOVA model that included sire and dam (within sire) as random effects, and parity and year of calving as fixed effects.The results revealed substantial variation in all studied traits. The mean TMY was 5820.7 kg, with a high coefficient of variation (40.97%). The average PMY was 231.6 kg/week, and cows reached their peak yield around the 5th week. The analysis of variance indicated that the year of calving had a highly significant (P < 0.0001) influence on TMY and LL. The maternal effect (Dam within Sire) was significant for the post-peak decline rate (c) (P < 0.0001) and for TMY (P = 0.0018). In contrast, the sire effect and parity did not significantly affect most of the curve parameters or production traits. It concluded that the study concludes that annual environmental and management factors (year of calving) are the primary drivers of total milk production and lactation length in this herd. Maternal effects are crucial for lactation persistency. The high variability in key traits presents an opportunity for genetic improvement; however, enhancing overall herd management remains the most critical strategy for boosting productivity, as most traits were predominantly influenced by environmental conditions.